Comparison of Abandoned Land Utilization to Empower Vulnerable Communities in Obtaining Legal Justice - Permata Intan Maharani; Rini Fidiyani (Universitas Negeri Semarang, 2026)
Land plays an important role in supporting social welfare and economic development of the community. In Indonesian agrarian law, land must fulfill its social function so that it can benefit the wider community. However, in practice, there is still land that is not being used for its intended purpose and can be categorized as abandoned land, while on the other hand, vulnerable communities still experience limited access to land resources. This study aims to analyze the government's responsibility in guaranteeing access to land use for vulnerable communities as an effort to realize legal justice, as well as to compare the implementation of abandoned land use in the Administrative City of South Jakarta and the City of Semarang. This study uses a qualitative approach with a sociological juridical method that examines legal provisions and their implementation in society. Data was obtained through interviews with informants and literature studies related to land policy. The results of the study show that the state has a constitutional responsibility to guarantee community access to agrarian resources. However, the utilization of abandoned land as a means of empowering vulnerable communities in urban areas faces limitations due to limited land availability, high population density, and high economic value of land. Therefore, community empowerment is mostly carried out through other land policies such as land certification programs, asset legalization, and community economic empowerment programs. These findings indicate that land policies need to be adjusted to regional characteristics so that the goals of social justice and improved community welfare can still be achieved.